2010
DOI: 10.3346/jkms.2010.25.12.1727
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of Diphtheria-tetanus Vaccine in Adults

Abstract: This study was conducted to evaluate the immunogenicity and safety of diphtheria-tetanus (Td) vaccine in adults over 40 yr old who had never received a diphtheria-tetanus-pertussis (DTP) vaccination. A total of 242 subject completed three-doses of Td vaccination and subsequent assays for immunogenicity. Before vaccination, 33.9% and 96.7% participants showed antibody levels of diphtheria and tetanus, respectively, which were below protective level (<0.1 U/mL). After the first dose of Td vaccine, 92.6% and 77.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
3
18
0
2
Order By: Relevance
“…In most countries, booster immunization of diphtheria and tetanus is recommended to be performed every 10 years. Booster tetanus-diphtheria (Td) vaccine is recommended to start at the age of 11-12 years old [13]. Cigarette smoking has local and systemic effects on the immune system and increases the susceptibility to infections and also alter the course of infectious diseases [6].…”
Section: Introductionmentioning
confidence: 99%
“…In most countries, booster immunization of diphtheria and tetanus is recommended to be performed every 10 years. Booster tetanus-diphtheria (Td) vaccine is recommended to start at the age of 11-12 years old [13]. Cigarette smoking has local and systemic effects on the immune system and increases the susceptibility to infections and also alter the course of infectious diseases [6].…”
Section: Introductionmentioning
confidence: 99%
“…There are few immunogenicity studies concerned with Td vaccines, with especially limited data in adolescents. However, variable booster immune responses to Td vaccines have been reported in previous studies (13-16). These investigators suggest that the extent of the antibody levels after Td vaccinations may show inter-individual variability depending on immune responses, different individual vaccination backgrounds, and different Td vaccines.…”
Section: Discussionmentioning
confidence: 81%
“…The common local adverse reactions include pain in the injection site (55%) followed by swelling (13.9-19.8%) and redness (13.9-19.6%). Systemic adverse reactions include headache (30.9-37.5%), fatigue (30.9-37.5%), gastrointestinal problems (6.9-17.4%) and fever (5.4-5.6%) (13, 17-19). According to Lee et al (12), the local adverse reaction rate and systemic adverse reaction rate in Korean children was 82.6% and 25%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that the mean antibody levels of diphtheria and tetanus were inversely related with age [11]. Kulkarni et al screened 62 male subjects for assessing the immunogenicity of Td vaccine.…”
Section: Discussionmentioning
confidence: 99%